The Vascularity and Osteogenesis of a Vascularized Flap for the Treatment of Scaphoid Nonunion: The Pedicle Volar Distal Radial Periosteal Flap. (July 2019) - Tanner, Cary; Johnson, Toby; Majors, Alex; Hentz, Vincent R.; Husak, Lisa; Walker Gallego, Edward; Christ, Brad; Hoekzema, Nathan
Background: Vascularized periosteal flaps from the distal radius have been previously proposed. The purpose of this study was to investigate the vascularity and osteogenic potential of a vascularized volar distal radial periosteal flap for the treatment of scaphoid nonunion.Methods: In 5 fresh frozen cadavers, a rectangular periosteal flap was elevated from the distal radius with the pedicle just proximal to the watershed line. Latex dye was injected into the radial artery proximally and the vascularity of the flap characterized by microscopic evaluation. Patients with scaphoid nonunion were then treated with open reduction, internal fixation, and distal radius cancellous bone graft. Two groups of patients with midwaist nonunion scaphoid were then evaluated. The first group received the vascularized periosteal flap and the second group received a nonvascularized periosteal flap. A third group of proximal pole nonunions also received the vascularized flap.Results: Cadaveric dissections revealed that all of the injected flaps demonstrated vascularity to the distal edge of the flap. Vascularized flaps formed visible bone on imaging in 55% of cases. None of the nonvascularized flaps formed visible bone. In group 1, 12/12 midwaist nonunions united. In group 2, union was achieved in 6/6 of patients who completed the follow-up. In group 3, 6/7 proximal pole fractures united.Conclusions: Previously proposed vascularized periosteal flaps from the distal radius appear to possess notable osteogenic potential that may be of interest to surgeons treating scaphoid nonunion.